Ibn Qayyim al-Jawziyyah’s Educational Philosophy: A Framework for Contemporary Muslim Parenting - M Ridhona Z Nur (Sufiya Journal of Islamic Studies, 2023)
The thought of Ibn Qayyim al-Jawziyyah is positioned as a theoretical lens for re-examining the concept of child education in a holistic and integrative manner. This study aims to systematically describe the concept of tarbiyah in Ibn Qayyim’s thought and to construct its relevance to parenting practices in Muslim families. The research employed a library research method by using Ibn Qayyim’s works as primary sources, supported by secondary literature in the form of books, scientific journal articles, and other relevant academic sources. Data were analyzed using a descriptive-analytical approach through the stages of data reduction, thematic categorization, narrative presentation, and conceptual conclusion drawing. The findings reveal that Ibn Qayyim’s concept of tarbiyah establishes a comprehensive system of child education encompassing seven interrelated dimensions: tarbiyah imaniyyah (faith education), ruhiyyah (spiritual education), fikriyyah (intellectual education), khuluqiyyah (moral education), ijtimā‘iyyah (social education), badaniyyah (physical education), and jinsiyyah (sexual education), all of which are integrated in shaping the child’s holistic personality. Education, therefore, is understood as a process of forming existential awareness that connects spiritual, intellectual, moral, social, and biological dimensions within a unified educational framework. This study emphasizes that parenting in Islam constitutes a comprehensive process of instilling educational values from early childhood. Thus, the contribution of this study lies in reconstructing classical Islamic thought into a more applicable, contextual, and transformative discourse on contemporary parenting for strengthening Muslim family education.